Teasing Apart the Impact of Illness and IQ on Functional Neuroimaging Findings in Schizophrenia - Graham, Steven; Oh, Tomasina M.; Manning, Victoria; Jiang, Jiaying; Berne, Yeh Ing; Sim, Kang; McKenna, Peter J. (European Scientific Journal, ESJ, 2019)
Schizophrenia is a major psychiatric disorder associated with cognitive impairment. Functional brain imaging (fMRI) studies of schizophrenia patients reveal a complex pattern of brain differences in the prefrontal cortex. Both decreased (hypofrontality) and increased (hyperfrontality) activity have been reported in patients – inconsistencies that this paper argues could be explained by differences in IQ between patients and healthy controls. This study demonstrates a novel method to tease apart IQ and schizophrenia effects on brain activity. Twelve schizophrenia patients were matched to twelve healthy controls matched to patients’ estimated (premorbid) IQ before their illness, and twelve healthy controls matched to patients’ measured current IQ. All participants performed an executive function event-related fMRI task. Schizophrenia patients’ mean behavioral scores fell numerically between those of both control groups, and did not differ significantly from either group. Two distinct patterns of brain activity were found that were consistent with an effect due to either IQ impairment or schizophrenia diagnosis. Schizophrenia patients’ relatively reduced activity in middle/superior frontal (BA6/BA8) regions was related to their schizophrenia diagnosis, whereas their relatively increased activity in inferior frontal (BA44/45) and left middle frontal (BA8/9) regionsrelated instead to their current IQ impairment. These findings indicate that some fMRI differences reported in schizophrenia patients are artefacts of IQ matching. After removing the IQ confounds, schizophrenia was associated with lateral frontal hypoactivations and medial frontal failure of deactivation. This paper proposes a method to address IQ matching-related issues when studying populations where their illness involves cognitive deterioration.